Aplicación de las ecuaciones de energía y de cantidad de movimiento en el cálculo de bloques de anclajes para tuberías - Rodríguez Santos, Josué (2014)
When installing pipes under internal pressure, there are changes in direction and in the assembling of special parts. Dynamic forces, thrusts or efforts tend to disengage them. That’s why building anchor blocks are essential. They will absorb the thrusts and efforts produced by fluid energy to guarantee the stability of the system. The bearing capacity of the anchor block is defined by two components: 1) the component due to the weight of the anchor block, and 2) the component generated by the friction force between the anchor block and the terrain. While for the straight pipe we can assume that the efforts and thrusts produced by the fluid are absorbed by soil compaction in the trench.